The politics of knowledge use in wastewater management – A systematic literature review - Leeuwerik, Roald Niels Christiaan; Kwong, Yim Ming Connie; Fujitani, Marie (Frontiers in Environmental Science, 2025)
Previous research demonstrates that stakeholders possess diverse knowledge concerning wastewater impacts and appropriate management strategies. Importantly, these different kinds of knowledge are situated in a political context that influences whose knowledge is used to shape local management. While a better understanding of drivers behind the use of knowledge may enable decision-makers to include more stakeholders, a comprehensive review of the state of the literature is still lacking. To address this, this paper systematically reviews gray and peer-reviewed literature published between 1990 and 2023 that explores the politics of knowledge use in wastewater management. The findings show that decision-makers adopt a wide range of management strategies and that various factors influence knowledge use across these strategies. Although there appears to be recognition of the value of more localized and alternative forms of decision-making, local “non-experts” knowledge is still commonly excluded, and decision-making remains strongly driven by legal, scientific, and engineering perspectives. This poses the risk of rendering management initiatives and outcomes less effective due to an ill-fit to local needs or lack of support. It is argued that improving transparency around knowledge use in decision-making, bridging different knowledge systems, and facilitating local decision-making are needed steps forward. Future research should determine how these recommendations can best be adapted to specific contexts.